AT1 Receptor Antagonism Is Proangiogenic in the Brain: BDNF a Novel Mediator - Alhusban, Ahmed (The American Society for Pharmacology and Experimental Therapeutics, 2013)
Candesartan is an angiotensin II type 1 receptor blocker (ARB) that has been to shown to limit ischemic stroke and improve stroke outcome. In experimental stroke, candesartan induces a proangiogenic effect that is partly attributable to vascular endothelial growth factor. Brain-derived neurotrophic factor (BDNF) is a member of the neurotrophin family that has been reported to have angiogenic effects and play an important role in recovery after stroke. The purpose of this investigation was to determine the role of BDNF in the proangiogenic effect of candesartan in the brain under hypertensive conditions. Accordingly, spontaneously hypertensive rats were treated with candesartan, and brain tissue samples were collected for quantification of BDNF expression. In addition, human cerebromicrovascular endothelial cells were treated with either low-dose (1 ƒM) or high-dose (1 µM) angiotensin II alone or in combination with candesartan (0.16 µM) to assess the effect of candesartan treatment and BDNF involvement in the behavior of endothelial cells. Candesartan significantly increased the expression of BDNF in the SHR (P < 0.05). In addition, candesartan reversed the antiangiogenic effect of the 1-µM dose of AngII (P = 0.0001). The observed effects of candesartan were ablated by neutralizing the effects of BDNF. Treatment with the AT2 antagonist PD-123319 significantly reduced tube-like formation in endothelial cells. AT2 stimulation induced the BDNF expression and migration (P < 0.05). In conclusion, candesartan exerts a proangiogenic effect on brain microvascular endothelial cells treated with angiotensin II. This response is attributable to increased BDNF expression and is mediated through stimulation of the AT2 receptor.